Analysis of Students’ Mathematical Disposition Ability in Online Mathematics Learning During the Pandemic - Ade Putri (Journal of Research on Mathematics Instruction (JRMI), 2022)
Mathematical disposition ability is a strong will from within students to learn mathematics so that students can solve mathematical problems. This ability is important for students because it can support their understanding of solving mathematical problems. This study analyzed students' mathematical disposition abilities in online learning mathematics during the pandemic. This research is quantitative descriptive research with the type of survey research. The research subjects were grade 11 science and social studies students at Mutiara Harapan High School, totaling 30 students. Data collection techniques used questionnaires distributed through google forms and interviews. The data analysis technique used descriptive statistics. The result is that the first 4 indicators of mathematical dispositional ability are in the high category with percentages of 72%, 79%, 75%, and 70%, respectively. The other 3 indicators are in the very high category, with percentages of 84%, 89%, and 84%, respectively. Overall, students' mathematical disposition during the pandemic was in the high category, with an average percentage of 79%. The mathematical disposition of students in the high category shows that students have self-confidence, flexibility, perseverance, curiosity, reflection on work results, and appreciation and apply the role of mathematics in everyday life.